Pengaruh Factor Kepercayaan, Pendapatan dan Pengetahuan terhadap Respon Konsumen Atas Majalah Elmahrusy dari Elmahrusy Media - Ayudianti, Indah (BUDGETING : Journal of Business, Management and Accounting, 2024)
This journal was written with the aim of analyzing the trust, income and knowledge factors that occur in MSME owners, namely the Elmahrusy magazine which is currently very popular. Data was collected by distributing questionnaires to class 12 students at the Arraoudhoh boarding school, Almahrusiyah Putri Lirboyo Islamic boarding school. Data analysis using descriptive analysis and several regression analyses, the results of this research show that trust, income and knowledge in Elmahrusy magazine influence consumer interest in buying and reading Elmahrusy magazine on Elmahrusy Media. In practical terms, it is hoped that the findings of this research will be useful for Elmahrusy Media as a consideration for determining further policies in looking at opportunities to achieve increased consumer interest in buying Elmahrusy magazines, because it has been proven that this research looks at the positive influence of trust, income and knowledge to increase the magazine's MSMEs. elmahrusy from elmahrusy media. Keywords: Income and Knowledge of Consumer Responses, Trust.